2015
DOI: 10.1186/s12983-015-0126-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical cues and pheromones in the sea lamprey (Petromyzon marinus)

Abstract: Chemical cues and pheromones guide decisions in organisms throughout the animal kingdom. The neurobiology, function, and evolution of olfaction are particularly well described in insects, and resulting concepts have driven novel approaches to pest control. However, aside from several exceptions, the olfactory biology of vertebrates remains poorly understood. One exception is the sea lamprey (Petromyzon marinus), which relies heavily upon olfaction during reproduction. Here, we provide a broad review of the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 115 publications
1
60
0
Order By: Relevance
“…Little evidence of genetic differentiation was documented among populations within each Great Lake basin, consistent with tagging studies (Bergstedt & Seelye, ) that have demonstrated lack of natal homing. Data on SNP allele frequency variation within Great Lakes basins relative to more substantial variation among basins are consistent with the hypothesis that adult sea lampreys select streams based on olfactory queues associated with larval abundance in streams rather than cues associated with natal origins (Buchinger, Siefkes, Zielinski, Brant, & Li, ).Previous analyses of sea lamprey spatial genetic structure in terms of genetic affinities among populations based on mtDNA (Waldman et al, ) and microsatellite loci (Bryan et al, ), and coalescence‐based model evaluation and estimation of levels of population bottlenecks (Bryan et al, ) indicated a sequential pattern of movements from Lake Ontario to Lake Erie and then into the upper Great Lakes.…”
Section: Discussionsupporting
confidence: 72%
“…Little evidence of genetic differentiation was documented among populations within each Great Lake basin, consistent with tagging studies (Bergstedt & Seelye, ) that have demonstrated lack of natal homing. Data on SNP allele frequency variation within Great Lakes basins relative to more substantial variation among basins are consistent with the hypothesis that adult sea lampreys select streams based on olfactory queues associated with larval abundance in streams rather than cues associated with natal origins (Buchinger, Siefkes, Zielinski, Brant, & Li, ).Previous analyses of sea lamprey spatial genetic structure in terms of genetic affinities among populations based on mtDNA (Waldman et al, ) and microsatellite loci (Bryan et al, ), and coalescence‐based model evaluation and estimation of levels of population bottlenecks (Bryan et al, ) indicated a sequential pattern of movements from Lake Ontario to Lake Erie and then into the upper Great Lakes.…”
Section: Discussionsupporting
confidence: 72%
“…Petromyzon marinus is a jawless vertebrate that uses a multicomponent pheromone during reproduction (Teeter, 1980;Buchinger et al, 2015). Parasitic lampreys reside in streams as juveniles for several years, emigrate downstream into lakes or oceans to feed on fish, and return to streams to spawn.…”
Section: Introductionmentioning
confidence: 99%
“…The application of this method to samples of lake water conditioned with sea lamprey larvae provides estimates of the release patterns and enantiomer ratios of the putative pheromones. Overall, the quantification of petromyroxol enantiomers will enhance behavioural tests to fully determine their functions as migration pheromones in a model species of vertebrate pheromone . The developed method exemplified a hyphenated mass spectrometric technique applied as an efficient approach to chiral quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The sea lamprey ( Petromyzon marinus ) is a parasitic vertebrate in the Laurentian Great Lakes, whose invasion resulted in major ecological disaster. Pheromone communication in sea lamprey is increasingly well understood and it has been shown that they rely on pheromones during migration and reproduction . Therefore, pheromones could be potentially targeted as a control tool for managing the invasive populations of sea lamprey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation